The relative age effect in team sport: What if we look at it from a different view? - Silva, A. S.; Barreiros, A.; Fonseca, A. M. (Talent Development & Excellence, 2016)
We aimed to compare the prevalence of the relative age effect (RAE) - year and quarter of birth - in several generations simultaneously and in independent cohorts. The sample included 502 athletes (287 men; 215 women), who competed in the national teams between the 1986/87 and 2010/11 seasons. The sample was divided into eight cohorts of each gender. The initial analysis demonstrated a significant RAE (quarter and year of birth) in both genders. The final analysis demonstrated that in the male sample the RAE does not exist in the birth quarter in any cohort, and in the birth year it only exists in some cohorts for both genders. Furthermore, we found a significant RAE in the senior category, at least in one cohort in both genders.